The dynamics of job creation and destruction for University graduates : why a rising unemployment rate can be misleading - Cardoso, Ana Rute (2002)
This study uses a matched employer-employee data set on the Portuguese economy to analyze systematic information on job creation and job destruction for university graduates, compared to other groups of workers. We find that the unemployment rate can provide a misleading idea of the dynamics in labor demand and of the employment prospects for university graduates. The pessimistic view that seems to be popular nowadays, stating that the expansion of higher education may have gone too far and that investment in a higher education degree has become a too risky business, possibly not worthwhile, as employers are no longer keen on recruiting newly graduate workers, does not find support in the empirical evidence for the Portuguese economy.